Trancatheter embolization of pulmonary artery pseudoaneurysm with detachable coils in association with non-adhesive liquid embolizing agent (Squid): Rare pulmonary artery lesion: innovative approach. - Piacentino, Filippo; Fontana, Federico; Curti, Marco; Imperatori, Andrea; Venturini, Massimo (Acta Biomedica Atenei Parmensis, 2021)
A nodular lesion at the lower left pulmonary lobe was detected in a 46 years old male during a preoperative chest X-Ray for appendicitis. To further characterise the nodule, a contrast enhanced computed tomography (CE-CT) was performed showing a 20 mm vascular lesion, which was suspected to be a pseudoaneurysm. The diagnostic angiography detected a flattening of the vascular wall with a voluminous pseudoaneurysm (PSA) in the distal portion of the tributary branch of the inferior left lobe. To treat the lesion, a 2.9F microcatheter was advanced into the sac and 4 detachable coils were placed (16-18mm Penumbra Inc) to pack the PSA. To block vascular supply to the lesion, the feeding artery was embolized with an ethylene vinyl alcohol copolymer agent (Squid Peri 18, Emboflu). The final angiographic control showed the exclusion of the pseudoaneurysmal sac which was confirmed by SEMAR™ reconstructed CE-CT scan after 40 days. Furthermore, no signs of pulmonary infarction were reported. (www.actabiomedica.it)